Prevalence of Rheumatic Heart Disease in First-degree Relatives of Index-cases: A Systematic Review and Meta-Analysis - Antonio Mutarelli; Guilherme Paes Gonçalves Nogueira; Alexandre Negrao Pantaleao; Alleh Nogueira; Bruna Giavina-Bianchi; Isabella M. Gonzalez Fonseca; Bruno R. Nascimento; Walderez O. Dutra; Robert A. Levine; Maria C. P. Nunes; On behalf of PRIMA Network (Global Heart)
Background: Rheumatic heart disease (RHD) is the leading cause of cardiac death in children, with over 300,000 annual fatalities. Immunological, genetic, and environmental factors contribute to an increased risk of RHD. It remains unclear whether first-degree relatives have a higher RHD prevalence than the regional average. Methods: We performed a systematic review and meta-analysis of echocardiographic screening studies reporting the prevalence of RHD in family members of individuals with RHD or acute rheumatic fever. PubMed, Embase, Cochrane, and Lilacs databases were searched. Finding Forrester RHD was classified as per the 2012 World Heart Federation criteria. Random-effects models assessed definite RHD prevalence in study groups. Results: Four of the 1160 studies were included, with 776 first-degree relatives screened. Two studies were from Africa, one from South America, and one from Oceania. In the first-degree relatives of index cases, the prevalence of RHD was 7% (95% confidence interval [CI] 3.7-13). The control group, individuals screened with no known RHD cases in their family, had a lower prevalence than first-degree relatives (risk ratio [RR] 0.44, 95% CI 0.26-0.75). There was no difference in the prevalence of RHD among siblings and parents of cases. Conclusion: There is an overall prevalence of non-relatives from the respective region, which suggests that genetic predisposition may play a role. In future studies of RHD, the systematic screening of first-degree relatives should be considered with a better control group—socioeconomic, region, age, and sex-matched.